2001
DOI: 10.1046/j.1420-9101.2001.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Moving in two worlds: aquatic and terrestrial locomotion in sea snakes (Laticauda colubrina, Laticaudidae)

Abstract: Yellow‐lipped sea kraits (Laticauda colubrina) are amphibious in their habits. We measured their locomotor speeds in water and on land to investigate two topics: (1) to what degree have adaptations to increase swimming speed (paddle‐like tail etc.) reduced terrestrial locomotor ability in sea kraits?; and (2) do a sea krait’s sex and body size influence its locomotor ability in these two habitats, as might be expected from the fact that different age and sex classes of sea kraits use the marine and terrestrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
88
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(99 citation statements)
references
References 27 publications
9
88
1
Order By: Relevance
“…This assumption is supported by previous reports of snake behaviour (e.g. Saint Girons 1964, Guinea 1986) and by the marked impairment of a snake's swimming ability caused by a prey item in the stomach (Shine & Shetty 2001). Sea kraits are vulnerable to predators such as sharks (Ineich & Laboute 2002) and therefore apparently return to land as soon as they have fed.…”
Section: Discussionsupporting
confidence: 67%
“…This assumption is supported by previous reports of snake behaviour (e.g. Saint Girons 1964, Guinea 1986) and by the marked impairment of a snake's swimming ability caused by a prey item in the stomach (Shine & Shetty 2001). Sea kraits are vulnerable to predators such as sharks (Ineich & Laboute 2002) and therefore apparently return to land as soon as they have fed.…”
Section: Discussionsupporting
confidence: 67%
“…Although we attempted to select trials where fish moved at similar velocities, fish did not appear capable of moving at the same velocity across all treatments (Table1). However, other studies have also found that the very slowest gaits for aquatic locomotion are still faster than terrestrial locomotion for organisms that are primarily aquatic (Shine and Shetty, 2001;Pace and Gibb, 2009 , anterior body oscillations are minimal (Lauder and Tytell, 2006). Thus, it seems unlikely that our finding that anterior oscillations increase as the water level is lowered is because of the minimal velocity differences between our treatments (see 'Results').…”
Section: Materials and Methods Animalsmentioning
confidence: 64%
“…Despite the tractability and simplicity of elongate fish as a model system in which to address this question, few studies have directly compared axial-only locomotion in aquatic versus terrestrial environments. In addition, most such studies have considered only undulation frequency and/or overall animal velocity (Jayne, 1986;Shine and Shetty, 2001;Shine et al, 2003), with a much smaller subset encompassing other kinematic variables (Gillis, 1998;Ellerby et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…Species that specialize for particular environments often exhibit performance costs in contrasting environments [1,2]. In some cases, specializations following major habitat transitions become so extreme that a species might rarely, if ever, encounter the contrasting, ancestral habitat [3].…”
Section: Introductionmentioning
confidence: 99%